Flouting Conversational Maxims: A Pragmatic Analysis of Anne Hathaway’s Interviews on the Tonight Show - Setyadji, Bimantara; Wirawan, Johannes Raelis Aziel; Hazmi, Muhammad Raihan; Rahayu, Dwi (UM Purwokerto Press, 2025)
This research presents an examination of the flouting of conversational maxims in The Tonight Show Starring Jimmy Fallon, featuring Anne Hathaway as the guest. The objectives of this study are to identify which maxims are flouted by both the host and the guest, and to explore the underlying reasons for these violations. This analysis employs a qualitative method, with data sourced from a YouTube video. The primary research instrument consists of a transcript of the dialogue between Jimmy Fallon and Anne Hathaway that includes instances of flouted maxims. To identify and interpret the occurrences of maxim flouting, this study utilizes Grice’s theory of the Cooperative Principle, which comprises four categories of maxims: quantity, quality, relevance, and manner. The results of the study demonstrate that the maxim of quantity is the most frequently flouted with (50%) percentage, followed by relevance (29%), manner (14%), and quality (7%). Based on the results, the interaction in those interviews often relies on providing too much information, so the guest will mostly speak. The goal of this flouting is to give a sense of humor to engage the audience's interest in the conversation on this talk show.